Metallothionein Expression as a Physiological Response against Metal Toxicity in the Striped Rockcod Trematomus hansoni - Bakiu R.; Pacchini S.; Piva E.; Schumann S.; Tolomeo A. M.; Ferro D.; Irato P.; Santovito G. (International Journal of Molecular Sciences, 2022)
Metal bioaccumulation and metallothionein (MT) expression were investigated in the gills and liver of the red-blooded Antarctic teleost Trematomus hansoni to evaluate the possibility for this species to face, with adequate physiological responses, an increase of copper and cadmium concentrations in its tissues. Specimens of this Antarctic fish were collected from Terra Nova Bay (Ross Sea) and used for a metal exposure experiment in controlled laboratory conditions. The two treatments led to a significant accumulation of both metals and increased gene transcription only for the MT-1. The biosynthesis of MTs was verified especially in specimens exposed to Cd, but most of these proteins were soon oxidized, probably because they were involved in cell protection against oxidative stress risk by scavenging reactive oxygen species. The obtained data highlighted the phenotypic plasticity of T. hansoni, a species that evolved in an environment characterized by naturally high concentrations of Cu and Cd, and maybe the possibility for the Antarctic fish to face the challenges of a world that is becoming more toxic every day.